Simple website development training as an effort to improve students' hard skills at SMK Negeri 3 Tegal - Dairoh, Dairoh; Wiyono, Slamet; Ratono, Ratono (Community Empowerment, 2021)
SMKN 3 Tegal has adequate ICT and is located in the heart of Tegal City and has a computer network major. This dedication is aimed at increasing hard skill knowledge through web development training. The activity which was attended by 30 participants was carried out by providing simple web basic theory, practice and web development assistance. The results of this activity show that participants can understand how to create a web, use, process, run and manage a simple web with a success rate of 87%.